2016
DOI: 10.1097/01.prs.0000481102.24444.72
|View full text |Cite
|
Sign up to set email alerts
|

Seroma in Prosthetic Breast Reconstruction

Abstract: Risk, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 109 publications
2
94
1
7
Order By: Relevance
“…[2] A closed suction drain in the surgical field can decrease seroma formation and possibly reduces the risk of infection. [3,4] However, prolonged drain duration may increase infection rate due to ascending infection. [57] The optimal timing of drain removal after prosthesis-based breast reconstruction is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[2] A closed suction drain in the surgical field can decrease seroma formation and possibly reduces the risk of infection. [3,4] However, prolonged drain duration may increase infection rate due to ascending infection. [57] The optimal timing of drain removal after prosthesis-based breast reconstruction is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Chun et al [1] reported that the use of ADM increased the risk of seroma occurrence by 4.24 times, and of infection by 5.37 times, whereas Parks et al [11] reported that it increased the risk of seroma by almost 2 times. Furthermore, Jordan et al [7] reported that such an increase in the occurrence of seroma multiplied the chance of tissue expander removal by 4.42 times and of infection-induced tissue expander removal by 6.71 times [12]. However, other studies reported no significant association between the use of ADM and seroma formation [13,14].…”
Section: Discussionmentioning
confidence: 96%
“…If a drain is hastily removed before drainage decreases adequately, seroma can occur [7,11,15,16]. Few studies have reported the exact removal time of the drain postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations